Correction: the oxygen reduction reaction catalyzed by Synechocystis sp. PCC 6803 flavodiiron proteins. Issue 1 (13th November 2019) - Brown, Katherine A.; Guo, Zhanjun; Tokmina-Lukaszewska, Monika; Scott, Liam W.; Lubner, Carolyn E.; Smolinski, Sharon; Mulder, David W.; Bothner, Brian; King, Paul W.
Abstract : Correction for 'The oxygen reduction reaction catalyzed by Synechocystis sp. PCC 6803 flavodiiron proteins' by Katherine A. Brown et al., Sustainable Energy Fuels, 2019, DOI: ; 10.1039/c9se00523d .